0.1% Nepafenac reduces pain and increases patient comfort during cataract surgery. Issue 5 (October 2018) - Oğurel, Tevfik; Oğurel, Reyhan; Onaran, Zafer; Örnek, Kemal
Abstract: Purpose: To evaluates analgesic effectiveness of 0.1% nepafenac during cataract surgery. Methods: This prospective randomized randomized double-masked, placebo-controlled study comprised 80 eyes of 40 consecutive patients who underwent bilateral cataract surgery and implantation of foldable intraocular lens with topical anesthesia with and without topical nepafenac drops. Each eye of patients was assigned to group 1 and group 2. Topical anesthesia combined with 0.1% nepafenac used three times a day the day before the surgery and once half an hour just before the surgery was group 1, consisting of 40 eyes, and topical anesthesia with using placebo was group 2 consisting of 40 eyes. Patients were asked to score their pain using a visual analog scale (VAS) and verbal pain scale (VPS) immediately following the surgery. When the patient moved or squeeze the eye during surgery, the surgical comfort was evaluated as bad and otherwise, it was evaluated as good. Results: When the intensity of pain during the surgery was evaluated, the percentage of patients reporting mild or no pain in group 1 was %825 and in group 2 was %45. Mean VAS pain score and mean VPS pain score in group 1 was significantly lower than that in group 2(p = 0.024, p < 0.001). Surgical comfort in group 1 was %825 and in group 2%65(P = 0.075). Conclusion: 0.1% nepafenac reduces pain of patients who undergone routine clear corneal phacoemulsification with topical anesthesia and may increase patient comfort during the surgery when used preoperatively.